Beryllium Mineralogy of the Kola Peninsula, Russia—A Review - Lyudmila M. Lyalina; Ekaterina A. Selivanova; Dmitry R. Zozulya; Gregory Yu. Ivanyuk (Minerals, 2018)
This paper reviews the available information on the beryllium mineralogy of the different type of occurrences in the Kola Peninsula, northwest Russia. Beryllium mineralization in the region is mainly associated with alkaline and felsic rocks, which differ significantly in petrological, geochemical, mineralogical features and age. In total 28 beryllium minerals are established on the Kola Peninsula up today. Beryl is one of the ore minerals in the differentiated granite pegmatites of the Kolmozerskoe lithium deposit. A large diversity of beryllium minerals occur in the pegmatites and hydrothermal veins formed in the late stages of the Lovozero and Khibiny alkaline massifs. Most of these minerals, as leifite, lovdarite, odintsovite, sphaerobertrandite and tugtupite are rare in other environments and have unique properties. These minerals formed under conditions of extreme alkalinity and their formation was favored by abrupt changes in the alkalinity regimes. Some of minerals, as chrysoberyl in xenoliths of hornfels, genthelvite and unique intergrowth of meliphanite and leucophanite formed in contrasting geochemical fronts between felsic/intermediate and mafic rocks.